(Dis)ability-informed mentors support occupational performance for college students with learning disabilities and attention-deficit/hyperactivity disorders through problem-solving and a focus on strengths. (May 2021) - Kreider, Consuelo M; Medina, Sharon; Koedam, Hannah M.
Introduction: Students with learning disabilities and attention-deficit/hyperactivity disorder are well represented on college campuses. However, they experience challenges to meeting occupational and role expectations associated with being in college. Mentors serve as natural supports for young people within college environments. This study investigates the ways in which graduate-student mentors, who were supported in understanding learning disabilities and attention-deficit/hyperactivity disorder and their mentee's strengths and challenges through an occupational lens, provided problem-solving supports for undergraduate mentees with learning disabilities and attention-deficit/hyperactivity disorder. Methods: Thematic qualitative analysis was used to investigate problem-solving supports provided by mentors ( n = 57) of undergraduate mentees ( n = 52) with learning disabilities and attention-deficit/hyperactivity disorder. Results: Three themes, executive functioning, adult life skills, and academics, represent areas in which mentors worked with mentees in guiding and co-creating strategies to address academic, social, and daily life challenges. Mentors' understanding of their mentees' disability-related challenges and strengths within everyday life situations was important for fostering the occupational performance of mentees. Conclusion: The inclusion of biopsychosocial approaches is needed in the development of disability-related mentorship interventions where occupational therapists can leverage disciplinary understanding of disabilities and the fostering of occupational performance to support social functioning and participation in college.